Strategi Peningkatan Kinerja Bisnis Usaha Mikro Kecil Menengah (Studi Pada UMKM Makanan Dan Minuman Nasabah KUR Bank Syariah Indonesia Area Bandung Kota) - Fajar, Mohammad; Syarief, Rizal; Yusri, Doni (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2025)
Bank Syariah Indonesia as one of the state-owned banks has an interest in the success of the people's business credit (KUR) financing program launched by the government. The objectives of this study are: (1) to analyse the effect of financial literacy on the business performance of food and beverage (F&B) SMEs; (2) to analyse the effect of financial inclusion on the business performance of F&B SMEs; (3) to analyse the effect of entrepreneurial orientation on the business performance of F&B SMEs; (4) to analyse the effect of social media marketing capability on the business performance of F&B SMEs: (4) analyse the effect of social media marketing capability on business performance of mamin SMEs; and (5) formulate strategies to improve business performance of F&B SMEs. Data collection using the slovin method, where the sample size was set at 283 respondents. Research with descriptive and inferential statistical methods using multiple linear regression analysis, which consists of validity test, reliability, t test, F test. Strategy formulation using internal-external environmental analysis with IFE and EFE matrix, position mapping and alternative strategies with IE and SWOT matrixs, then determine strategy priorities with QSP matrix. The results of the analysis show that food and beverage SMEs are in quadrant I (grow and build). Based on the results of quantitative analysis on the QSP matrix, the strategy that can be implemented is assistance in preparing financial reports of SMEs to maintain financial stability.